Enhancing classification of preterm-term birth using continuous wavelet transform and entropy-based methods of electrohysterogram signals - Romero-Morales, Héctor; Muñoz-Montes de Oca, Jenny Noemí; Mora-Martínez, Rodrigo; Mina-Paz, Yecid; Reyes-Lagos, José Javier (Frontiers in Endocrinology, 2023)
Despite numerous research, premature birth's electrophysiological mechanisms are not fully understood. Prediction of preterm birth contributes to child survival by providing timely and skilled care to both mother and child. Electrohysterography is an affordable, noninvasive technique that has been sensitive in diagnosing preterm labor. This study aimed to choose the more appropriate combination of characteristics, such as electrode channel and bandwidth, in addition with linear, time-frequency, and nonlinear features of the electrohysterogram (EHG) for predicting preterm birth using classifiers. We analyzed an open-access dataset of 30 minutes of EHG obtained in regular checkups of women around 31 weeks of pregnancy who experienced premature labor (P) and term labor (T). The current approach filtered the raw EHGs in three relevant frequency subbands (0.3–1 Hz, 1–2 Hz, and 2–3 Hz). The EHG time series were then segmented to create 120-second windows, from which individual characteristics were calculated. The linear, time-frequency, and nonlinear indices of EHG of each combination (channel-filter) were fed to different classifiers using feature selection techniques. The best performance, i.e., 88.52% accuracy, 83.83% sensitivity, and 93.22% specificity was obtained in the 2–3 Hz bands using Medium Frequency, Continuous Wavelet Transform (CWT), and entropy-based indices. Interestingly, CWT features were significantly different in all filter-channel combinations. The proposed study uses small samples of EHG signals to diagnose preterm birth accurately, showing its potential application in the clinical environment. Our results also suggest that CWT and novel entropy-based features of EHG could be descriptors for analyzing and understanding the complex nature of preterm labor mechanisms.